KAJI BANDING METODA PENGAJARAN SANGGAR MENGGAMBAR DALAM KONTEKS PERKEMBANGAN BAHASA RUPA ANAK DI BANDUNG - I NYOMAN NATANAEL (Serat Rupa: Journal of Design, 2016)
Drawing produced by the children is usually different from that produced by adults, because it has a distinctive visual language which is universal and can be classified as an earlier visual language. It turns out the difference between the results obtained drawing of children who are not participating with children who are studying in the studio drawing. But there is also a difference in the drawing between children who learn in different drawing studio. This is caused partly because of the learning method taught to children. This study examines the impact of the learning method taught to children, in terms of visual language that appears on the results of the children's drawingsÂ Keywords: children; drawing; language; studio; visual